Buddhism and Vipassana Meditation: A Scientific Method for Mental and Social Growth in the Modern Age - Alok Kumar Verma (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2023)
Vipassana meditation, discovered by Buddha approximately 2500 years ago, is one of the oldest meditation techniques in India. This meditation technique is a non-denominational scientific technique of self-transformation through self-observation in society. This leads human society to a progressive and better insight and a positive health 1appearance. Vipassana meditation is a moral and social path that sees and develops humans from within nature through the outline of their mind and body. Hence, the main objective of this study is to examine the effect of Vipassana meditation on mental health as well as to determine how its practice leads to the social development of society. Consequently, how is it beneficial to society and how does this meditation technique affect mental and physical health in society? Hence it can be said that through the practice of this meditation technique, a powerful and peaceful message can be delivered to the human mind. This paper shows that Vipassana meditation provides a variety of physical and mental benefits that greatly improve human well-being. These benefits include decreased stress, improved immune system function, decreased blood pressure and heart rate, increased sleep quality, and decreased chronic pain. Thus, the practice of Vipassana meditation has the potential to bring about profound transformative changes in human life.